Invasion and drought alter phenological sensitivity and synergistically lower ecosystem production. Issue 10 (27th August 2019) - Esch, Ellen H.; Lipson, David A.; Cleland, Elsa E.
Abstract: Climate change and shifting species composition have influenced ecosystem‐scale phenology worldwide. For instance, invasive plant species have greater vegetation phenological sensitivity to climate change than native plant species in some regions, and hence invasion could modify how ecosystem carbon gain responds to increased drought frequencies expected with climate change. Results from a 4‐yr drought experiment show that invasion reduced ecosystem potential for carbon gain via increased sensitivity to reduced rainfall. Using canopy greenness (Normalized Difference Vegetation Index, NDVI) as a proxy for potential ecosystem carbon gain, we show that areas invaded by herbaceous species had up to a 70% reduction in maximum NDVI under severe drought conditions as compared to areas dominated by native shrubs. Phenological differences between herbaceous‐ and shrub‐dominated vegetation contributed to this reduction in potential ecosystem carbon gain because invaded areas had delayed green‐up, especially under drought conditions, and shrub senescence was accelerated by drought. Hence, invasion by herbaceous species and increased drought frequencies are likely to act synergistically to reduce ecosystem capacity for carbon gain in this system. Our findings suggest that predicting ecosystem responses to future climate change could be improved by projecting of the spread of invasive species and accounting for phenological variation between native and invading species.